PROGRAM KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN REVENUE FOOD & BEVERAGE 11/12 ROOFTOP BAR SEMARANG SEBAGAI DESIGN & CREATIVE MANAGER - Irvinda Rafii Zharfansyah; S Rouli Manalu (Interaksi Online, 2026)
The food and beverage (F&B) industry in Semarang is marked by intense competition,resulting in fluctuating revenue at 11/12 Rooftop Bar due to promotional strategies that arenot yet fully effective. This study aims to implement an Integrated Marketing Communication(IMC) program with a focus on event marketing and sales promotion to improve revenueperformance. By integrating elements such as social media marketing, public relations, andadvertising, several programs including themed events and promotional offers were carriedout. The results show that these integrated activities were able to attract more visitors andcontribute to increased revenue during the program period. This study concludes that an IMCstrategy based on event marketing and sales promotion can effectively enhance businessperformance, especially in improving F&B revenue.